2016
DOI: 10.1116/1.4959576
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport and magnetic properties of cobalt telluride nanostructures

Abstract: Transition metal telluride CoTe nanostructures have been synthesized using a wet-chemical method. These nanostructures exhibit NiAs-type hexagonal crystal structure with a space group of P63/mmc. The magnetic measurements show spontaneous magnetization and hysteresis, and the coercivity increases with a decrease in temperature. The saturation magnetization was calculated to be around 0.2 μB/Co atom. The magnetic transition temperature was found to be above room temperature similar to that of the bulk CoTe. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…3,15,18 The second issue concerns the source of the magnetism observed in recent studies on nanostructured CoTe x materials. [9][10][11][12][13] Wang et al 1 carried out high-resolution x-ray photoelectron spectroscopy (XPS) on cobalt telluride branched nanostructured samples. They observed weak satellite peaks in their Co 2p 3/2 /2p 1/2 spectra which they attribute to elemental Co. 1 Wu et al 5 observed second phase fcc Co peaks in their XRD patterns from carbon supported CoTe 1.20 nanoparticles; the second phase peaks were reduced for higher heat treatment temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,15,18 The second issue concerns the source of the magnetism observed in recent studies on nanostructured CoTe x materials. [9][10][11][12][13] Wang et al 1 carried out high-resolution x-ray photoelectron spectroscopy (XPS) on cobalt telluride branched nanostructured samples. They observed weak satellite peaks in their Co 2p 3/2 /2p 1/2 spectra which they attribute to elemental Co. 1 Wu et al 5 observed second phase fcc Co peaks in their XRD patterns from carbon supported CoTe 1.20 nanoparticles; the second phase peaks were reduced for higher heat treatment temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still several recent reports in the literature of Co-Te nanostructured materials having the CoTe stoichiometry and being magnetic. [9][10][11][12][13] One such study reports CoTe nanowires a wells@phys.uconn.edu which exhibit ferrimagnetic behavior well above room temperature with a saturation magnetization of 0.2 µ B /Co. 10 Another report concerning CoTe nanotubes shows hysteresis loops with coercivity indicating ferromagnetic behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocomposites comprise a dimensional order class of nanomaterials, they can be formed by two or more atoms adding and improving the physical-chemical properties of the constituent elements [2], [3]. Several studies carried out through applications of nanocomposites based on cobalt, silicon or tellurium have shown promise because of the excellent properties acquired or improved due to the joining of these elements, however a structure constituted from the three elements Co x Si y Te z is still unknown, presenting short report in scientific literature or crystallographic database [4] - [6].…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Such change of resistivity can only be found in semimetals or narrow gap semiconductors 2326 . The logarithm of resistivity behavior above 200 K plotted against 1/T as shown in the inset can be fitted with a straight line, yielding an effective energy gap of 24 meV 27,28 . For temperatures lower than 200 K, the temperature dependence of resistivity can be written as .…”
Section: Introductionmentioning
confidence: 99%